Hubungan Gaya Hidup Aktif Terhadap Kebugaran Jasmani Peserta Didik SMP Negeri 21 Pontianak - Alfajar, Rizky (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The advent of globalization in Indonesia has led to the prevalence of habits in individuals' lives that neglect physical activity and an active lifestyle, consequently impacting physical fitness. Physical fitness is defined as the body's ability to adapt its organs to specific physical tasks. This study aims to investigate the relationship between an active lifestyle and the physical fitness of students at SMP Negeri 21 Pontianak. Employing a correlational research design, surveys were conducted using measurement tests and questionnaires to assess active lifestyle habits, while physical fitness was evaluated through the TKPN test. The study involved 128 ninth-grade students from SMP Negeri 21 Pontianak. Data analysis utilized the Karl Pearson product moment correlation coefficient at a significance level of 0.05. Findings revealed that 78 students (61%) exhibited a very good active lifestyle, while 50 (39%) demonstrated a good lifestyle. In terms of physical fitness, 82 students (64%) showed excellent performance, 42 (33%) were classified as good, and four individuals (3%) fell into the poor category. The correlation coefficient obtained was 0.438, indicating a moderate level of relationship between an active lifestyle and physical fitness. This underscores the importance of promoting an active lifestyle to enhance the physical fitness of students.Copyright © 2024 Rizky Alfajar, Andika Triansyah, Fitriana Puspa Hidasari